2014
DOI: 10.1093/aje/kwu101
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Education, Early Infections, and Antibiotic Use With Celiac Disease: A Population-Based Birth Cohort Study in Northeastern Italy

Abstract: We conducted a population-based birth cohort study of approximately 203,000 babies born in northeastern Italy (1989-2012) to investigate perinatal variables, early infections leading to hospital admission, and antibiotic use in the first 12 months of life as possible risk factors for celiac disease (CD). Incident CD cases were identified from pathology reports, hospital discharge records, and exemptions from prescription charges for clinical tests. Multivariate Poisson regression models were fitted to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 39 publications
7
123
0
5
Order By: Relevance
“…9 , 10 A population-based cohort study estimated that children who suffered from more than ten episodes of respiratory or gastrointestinal infections presented a higher risk of developing CD compared to children with less than four infection events. 11 Likewise, similar associations have been found by other epidemiological studies enrolling large cohorts and recording only the gastrointestinal infections. 12 , 13 These observations were based on parent or hospital reports where the causal pathogen was unidentified and subclinical infections were not considered.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…9 , 10 A population-based cohort study estimated that children who suffered from more than ten episodes of respiratory or gastrointestinal infections presented a higher risk of developing CD compared to children with less than four infection events. 11 Likewise, similar associations have been found by other epidemiological studies enrolling large cohorts and recording only the gastrointestinal infections. 12 , 13 These observations were based on parent or hospital reports where the causal pathogen was unidentified and subclinical infections were not considered.…”
Section: Introductionsupporting
confidence: 73%
“…12 , 13 These observations were based on parent or hospital reports where the causal pathogen was unidentified and subclinical infections were not considered. 11-13 …”
Section: Introductionmentioning
confidence: 99%
“…24 Using data from the Medical Birth Register, we included maternal age at delivery as a potential confounder because advanced maternal age at delivery has been positively associated with offspring TS 25 and may also be associated with offspring CD. 26 Type 1 diabetes is associated with TS 7 and CD. 27 In a sensitivity analysis, we therefore estimated the association between TS and CD after excluding individuals with type 1 diabetes.…”
Section: Covariatesmentioning
confidence: 99%
“…FVG is covered by a regional integrated healthcare system developed in the 1980s with the goal of automatically collecting and pooling data on healthcare funded by the national health service using a unique regional identification code. This system and data sources available in the region have been described in detail previously [14].…”
Section: Methodsmentioning
confidence: 99%
“…However, the same exposure has been scarcely investigated as a risk factor for coeliac disease [12,13]. In a large birth-cohort study based on record linkage of administrative data, we recently found a strong dose-dependent association between antibiotic exposure in the first 12 months of life and subsequent diagnosis of coeliac disease [14]. We therefore hypothesise that antibiotic consumption in the first months of life may explain the possible association between coeliac disease and asthma.…”
Section: Introductionmentioning
confidence: 93%